ANALISIS TERHADAP PELAPORAN KEUANGAN SEGMEN PADA PT INDIKA ENERGY TBK DAN ENTITAS ANAK TAHUN 2019-2020 - Yani, Dhini Dwi; Dea Nur Isnayani; Tita Ulya Salsabila; Endang Kartini Panggiarti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Disclosure of financial statements is one of the things that must be done by companies that have gone public. One of the reports that must be disclosed in the financial statements is the segment financial report. This segment report itself aims to provide easy information regarding the profit contribution, assets, revenue and growth trends of the company's segments so that financial users can better assess the company's overall performance and risk. This study aims to analyze the reporting of business segments owned by PT Indika Energy Tbk from 2019-2020, by conducting a ten percent test of segment revenue, profit/loss and assets based on PSAK No. 5. Qualitative descriptive method is the method used in this study. The research data is based on secondary data in the form of annual reports. Meanwhile, data analysis was carried out quantitatively with a ten percent test, then described qualitatively. The results showed that out of the 4 segments owned by PT Indika Energy Tbk, only 2 segments met the reporting requirements, namely the energy type and energy resource segments. Meanwhile, the energy infrastructure segment and portfolio companies not need to be reported because they do not meet the ten percent test, both for revenue, profit/loss, and assets.